The Double-Track System Method to Prevent Narcotics Recidivism - Muhammad Selfano Hidayat; Fahmi Fairuzzaman (Proceeding International Conference Restructuring and Transforming Law, 2026)
Drug abuse is a serious problem facing many countries, including Indonesia, due to its negative impacts on public health, social stability, and the law enforcement system. The high number of drug offenders sentenced to prison indicates that conventional criminal justice approaches have not fully addressed the root causes of drug abuse. This situation also contributes to the increasing recidivism rate among drug abusers. Therefore, a criminal justice approach is needed that is not only oriented toward punishment but also toward the rehabilitation of offenders through the application of the double-track system. This study aims to analyze the implementation of the Double Track System in handling drug abusers and its effectiveness in preventing recidivism. The research method used is empirical juridical with a descriptive approach. Research data was obtained through a literature review of relevant laws and regulations, books, and scientific journals, and supported by field data through interviews and observations. The results show that the double track system provides a balance between criminal sanctions and disciplinary sanctions within the penal system for drug abusers. The implementation of medical and social rehabilitation as part of this system can assist the recovery process for drug addicts, enabling them to return to normal functioning in society. However, the implementation of this system still faces various obstacles, such as limited rehabilitation facilities, a lack of professional staff, and a law enforcement paradigm that still focuses on imprisonment. Therefore, strengthening rehabilitation policies and improving coordination between law enforcement agencies are necessary to ensure that the double-track system can be implemented effectively and run optimally.